The relative tariff ratio index - Ron Sandrey (New Zealand Institute of Economic Research (NZIER), 2000)
[...] In the final analysis the RTR is potentially a sound and useful measure for providing an indication of the relative effects of border protection. If offers interesting dynamic possibilities should the measure be updated annually, although the resource cost involved in widening the scope of the bilateral matrix provided above and updating it must be recognised notwithstanding the scope to operationalise much of work. We consider that the measure has something to offer as simple yet powerful tool.
Keywords: 330; Zolltarif; Vergleich; Welt